2022
DOI: 10.3390/nano12234196
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytotoxicity and Bioimaging of Nitrogen-Vacancy Nanodiamonds

Abstract: Nanodiamonds, due to their chemical inertness and biocompatibility, have found extensive uses in drug delivery and biomedical applications. Fluorescent nanodiamonds with fluorescent properties generated by nitrogen-vacancy defects have been intensively investigated for bioimaging, due to their high quantum yield and high photobleaching stability. In addition, the surface properties and particle size of nanodiamonds have significant impacts on cellular uptake and imaging quality. In this study, nitrogen-vacancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The zeta potential was found to be −33.4 ± 6.35 mV, which is consistent with milled NDs, which usually exhibit hydrogen/hydroxyl terminating groups on the surface. 23 The detonation NDs with surface amine groups were directly modied with PDI, i.e., without any further treatment. The molecular structure of the PDI is shown in Fig.…”
Section: Nds and Modication With Pdimentioning
confidence: 99%
See 1 more Smart Citation
“…The zeta potential was found to be −33.4 ± 6.35 mV, which is consistent with milled NDs, which usually exhibit hydrogen/hydroxyl terminating groups on the surface. 23 The detonation NDs with surface amine groups were directly modied with PDI, i.e., without any further treatment. The molecular structure of the PDI is shown in Fig.…”
Section: Nds and Modication With Pdimentioning
confidence: 99%
“… 22 For cell tracking, fluorescent NDs with different sizes and concentrations were investigated for cytotoxicity and uptake by mesenchymal stromal cells (MSCs). 23 Multiple imaging techniques including fluorescence imaging, atomic force microscopy, and 3D soft X-ray tomography were employed to investigate cancer cells with fluorescence NDs. 24 The long-term imaging potential of NDs was demonstrated by sentinel lymph node mapping, 37 days after injection of NDs in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the cell activity was more than 95% and NDs did not show any considerable toxicity in different cell types [ 287 ]. Fryer and coworkers [ 288 ] evaluated the cytotoxicity and fluorescence imaging capacity of nitrogen-vacancy NDs with sizes in the range of 40 to 90 nm. Results showed that as the size of NDs increased, the cytotoxicity of NDs decreased and NDs with size 90 nm indicated high cellular uptake and fluorescence intensity [ 288 ].…”
Section: Carbon-based Nanostructuresmentioning
confidence: 99%
“…Fryer and coworkers [ 288 ] evaluated the cytotoxicity and fluorescence imaging capacity of nitrogen-vacancy NDs with sizes in the range of 40 to 90 nm. Results showed that as the size of NDs increased, the cytotoxicity of NDs decreased and NDs with size 90 nm indicated high cellular uptake and fluorescence intensity [ 288 ]. Karpeta et al [ 289 ] investigated the cytotoxicity of NDs in different cell lines and studied NDs’ biological activities such as cell viability, lipid peroxidation, and level of reactive oxygen species.…”
Section: Carbon-based Nanostructuresmentioning
confidence: 99%
“…The DLS-PDI values of NDs synthesized by different methods are as follows. The detonation NDs exhibited PDI values ranging from 0.1 to 0.6, 33,119 HPHT NDs 32 and CVD NDs 120 exhibited PDI values ranging from 0.1 to 0.3, and laser ablation NDs provided PDI values of 0.5 after glycidol surface coating. 121 It should be noted that the PDI values are subject to variation based on experimental conditions and post-synthesis treatments.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%